2019
DOI: 10.1177/0019793919858332
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Licensing of Social Services and Nursing Home Quality: A Regression Discontinuity Approach

Abstract: Occupational licensing has grown dramatically in recent years, with more than 25% of the US workforce having a license as of 2008, up from 5% in 1950. Has licensing improved quality or is it simply rent-seeking behavior by incumbent workers? To estimate the impact of increased licensure of social workers in skilled nursing facilities (SNFs) on service quality, the authors exploit a federal staffing provision that requires SNFs of a certain size to employ licensed social workers. Using a regression discontinuit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…Today, Europe's regulated professions involve more than 50 million people or 22% of total employment (European Commission 2015a; Koumenta and Pagliero 2017). Evidence from the USA and the EU shows that such regulation has a significant impact on prices and labor mobility, while little to no evidence supports the claim that quality is higher (Kleiner 2000;Kleiner andKrueger 2010, 2013;Johnson and Kleiner 2017;Koumenta and Pagliero 2017;Bowblis and Smith 2018;Barrios 2018). It seems that such protection no longer serves its original purpose: according to the European Commission (2015a, p. 7), "many of these regulations are now disproportionate and create unnecessary regulatory obstacles to the mobility of professionals, lowering productivity" (cf.…”
Section: Regulations Of Goods and Service Marketsmentioning
confidence: 99%
“…Today, Europe's regulated professions involve more than 50 million people or 22% of total employment (European Commission 2015a; Koumenta and Pagliero 2017). Evidence from the USA and the EU shows that such regulation has a significant impact on prices and labor mobility, while little to no evidence supports the claim that quality is higher (Kleiner 2000;Kleiner andKrueger 2010, 2013;Johnson and Kleiner 2017;Koumenta and Pagliero 2017;Bowblis and Smith 2018;Barrios 2018). It seems that such protection no longer serves its original purpose: according to the European Commission (2015a, p. 7), "many of these regulations are now disproportionate and create unnecessary regulatory obstacles to the mobility of professionals, lowering productivity" (cf.…”
Section: Regulations Of Goods and Service Marketsmentioning
confidence: 99%
“…Under federal law, nursing homes with 121 or more beds are required to staff a licensed social worker full time. 9 certificate of need (CON) laws, another state-level policy, also indirectly impact nursing home size through placing a ceiling on the supply of nursing home beds. As shown in previous studies, CON laws result in larger nursing homes in the long run due to the substantial fixed (capital) cost of proving long-term care.…”
Section: Introductionmentioning
confidence: 99%
“…Research has also found licensing to be either detrimental or not significantly helpful to consumers, the very people licensing purportedly benefits and protects. Recent studies of occupations such as funeral provider, social worker, and certified public accountant have found licensing raises prices, in part through the aforementioned artificially increased wages (Pizzola and Tabarrok 2017), and produces little to no increase in quality (Bowblis and Smith 2018;Barrios 2018). Similarly, research on occupations such as midwife, cosmetologist, and teacher has shown more restrictive licensing regulations in the form of tighter scope-of-practice laws (Markowitz et al 2017), lengthier educational requirements (Simpson et al 2016), and higher minimum examination scores (Shuls 2017) do not lead to improved outcomes for consumers.…”
Section: Introductionmentioning
confidence: 99%